1980
DOI: 10.1203/00006450-198002000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Serum Prolactin and Respiratory Distress Syndrome in the Newborn

Abstract: SummaryProlactin levels were measured in cord blood by radioimmunoassay in 57 premature infants between 26 and 36 weeks of gestation. The level of prolactin was in the range of 20 to 600 ng/ ml. Twenty-three of the infants subsequently developed respiratory distress syndrome (RDS). The mean cord prolactin in the infants with RDS was 140 + 30.7 ng/ml, whereas in the healthy infants it was 276.4 + 26.4 ng/ml. Cord prolactin levels less than 140 ng/ml were associated with a high incidence of RDS: of 25 infants wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

1982
1982
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 11 publications
(11 reference statements)
1
13
1
Order By: Relevance
“…A similar relationship between plasma prolactin and tracheal fluid surfactant exists in the fetal lamb (253). A correlation between cord blood prolactin levels and the incidence of RDS has also been reported (252,254,255). Amniotic fluid prolactin levels correlated negatively with the L/S ratio, however (256).…”
Section: Prolactinmentioning
confidence: 91%
“…A similar relationship between plasma prolactin and tracheal fluid surfactant exists in the fetal lamb (253). A correlation between cord blood prolactin levels and the incidence of RDS has also been reported (252,254,255). Amniotic fluid prolactin levels correlated negatively with the L/S ratio, however (256).…”
Section: Prolactinmentioning
confidence: 91%
“…For exam ple, several authors had shown that a high prolactin level coincided with a low inci dence of RD syndrome and vice versa \Haitih et al, 1978;Gluckman et al, 1978;Smith et al, 1979]. But relating prolactin to respiratory compliance did not reveal any statistically significant relation [Schober et al, 1982], Compliance measurements after birth are suitable to classify patients for studies which investigate the benefit of therapies, especially various forms of ventilatory sup port.…”
Section: Discussionmentioning
confidence: 99%
“…Fur thermore, prevention of RDS by antenatal betamethasone administration is far more ef fective in female infants -the natural ratio of incidence of RDS of male: female of 1.7:1 becomes 3.4:1 following glucocorticoid treat ment [4,39]. In addition to the infant's sex, several studies suggest an association of lower levels of several hormones -thyroxine [7,12,42], prolactin [21,24,47], estrogen [ 10,31 ] -in cord blood and higher incidence of RDS.…”
Section: Introductionmentioning
confidence: 99%